2017
DOI: 10.3892/ol.2017.7394
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of CagA, c‑Met, PI3K and Beclin‑1 expressed in gastric cancer and their association with prognosis

Abstract: Gastric cancer (GC) is the fourth most common type of malignant tumor worldwide, and causes the second highest number of cancer-associated mortalities in 2012. Gastric tumorigenesis is a multistep and multifactorial process. In the present study, tissue microarray and immunohistochemistry analysis were used to detect cytotoxin-associated gene A (CagA), c-Met, phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) and Beclin-1 expression in 121 GC tumors and 120 normal gastric tissues. The clinical relevance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…We showed that high PI3K expression was associated with larger size, lymphatic metastasis, and advanced tumor stage. Other studies support our findings and demonstrate an association of PI3K expression with pathohistological factors and unfavorable outcomes in various solid tumors [36][37][38][39]. High expression of mTOR in our cohort was also associated with advanced tumor stage but not with any other analyzed parameter.…”
Section: Discussionsupporting
confidence: 91%
“…We showed that high PI3K expression was associated with larger size, lymphatic metastasis, and advanced tumor stage. Other studies support our findings and demonstrate an association of PI3K expression with pathohistological factors and unfavorable outcomes in various solid tumors [36][37][38][39]. High expression of mTOR in our cohort was also associated with advanced tumor stage but not with any other analyzed parameter.…”
Section: Discussionsupporting
confidence: 91%
“…The measurement and assessment of HGF activity have been crucial role in understanding the tumor microenvironment that prompt tumor metastasis and drug resistance[ 47 ]. The recent immunostaining experiment has presented that MET expression was significantly associated with lymphatic vessel invasion and poor overall survival (OS), implying that the expression of HGF/c-Met pathway might serve as a prospective predictive factor in patients with GC[ 50 , 51 ]. Interestingly, patients with a lower pretreatment HGF level showed a positive response to the treatment of trastuzumab.…”
Section: Current Topics Of Biomarkers In Gcmentioning
confidence: 99%
“…Independent studies have suggested that CagA, the H. pylori effector protein, stimulates cancer-associated signal transduction by forming a complex with MET [182][183][184]. Although there was no significant genotype-phenotype interaction between soluble MET protein and single nucleotide polymorphism (SNPs) of the CagA-related genes, after adding the genetic counts of these SNPs, the diagnostic value of MET protein to distinguish gastric cancer patients from normal individuals improved significantly [176].…”
Section: Iv-circulating Met Levels As Diagnostic and Prognostic Biomamentioning
confidence: 99%